PEMBERDAYAAN MASYARAKAT DENGAN SOSIALISASI HIDROPONIK MENGGUNAKAN METODE SISTEM WICK DI DESA MEDALKRISNA - Khairunnisa, Salma; Purwatini, Lucky; Chairunnisa, Nurlaila Maysaroh (An-Nizam, 2024)
Medalkrisna Village has a large agricultural land, with the majority of its agricultural products in the form of rice. However, vegetable production in this village is still low, due to the lack of knowledge and understanding of the community about the cultivation of horticultural crops or vegetables. In fact, vegetable cultivation is quite flexible and can be done in the yard of the house, which has the potential to increase productivity in the area. Therefore, a community empowerment program is carried out through hydroponic socialization using the wick system method. This program aims to empower and improve the technical and non-technical skills of the community in the agricultural sector. The activity began with an explanation of the theory and practice of using pakcoy mustard plants as examples, including sowing seeds, applying the axis system, transplanting, and ending with a discussion session. The results of this activity show that the hydroponic cultivation of the wick system has succeeded in empowering the people of Medalkrisna Village in utilizing available land, especially the yard of the house. The community responded positively to this program, considering it useful and of high value to them.